A novel low-dimensional heteroatom doped Nd2O3 nanostructure for enhanced electrochemical sensing of carbendazim. (20th August 2019) - Zhou, Yuanzhen; Li, Yang; Han, Ping; Dang, Yuan; Zhu, Mengyi; Li, Qian; Fu, Yile
Abstract : Reasonable design and synthesis of high-efficiency nanocatalysts are of great significance for studying the electrocatalytic analysis of fungicides. Abstract : Reasonable design and synthesis of high-efficiency nanocatalysts are of great significance for the electrocatalytic analysis of fungicides. In this paper, La-doped Nd2 O3 (La-Nd2 O3 ) nanomaterials are synthesized by a hydrothermal method and characterized via SEM, TEM, EDS, XPS and XRD. The results confirm that the trigonal Nd2 O3 and La-Nd2 O3 are successfully synthesized, and La is localized on the surface of the Nd2 O3 lattice. Compared with Nd2 O3, La-Nd2 O3 nanomaterials have a larger surface area. In addition, the prepared Nd2 O3 and La-Nd2 O3 catalysts coated on a carbon paste electrode (CPE) are used as working electrodes to investigate their electrochemical performance for carbendazim (CBZ). Probably due to the synergistic electronic transfer process and dual-function effects of La-Nd2 O3, the La-Nd2 O3 modified electrode exhibits a stronger redox signal and faster electron transfer rate, thus resulting in superior electrocatalytic activity against CBZ. The proposed CBZ sensor produces a wide linear range of 0.08 to 50 μM and a low detection limit (0.027 μM, S/N = 3) by differential pulse voltammetry (DPV). Moreover, the La-doped catalyst has a long-term electrochemical activity and catalytic stability under steady state conditions, which indicates that La-Nd2 O3 is a promising catalyst in electrocatalysis and sensing applications.